Problems Encountered by the Person Deprived of Liberty in Quezon City Jail: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the problems encountered by a person deprived ofliberty in terms of health and medical services, peace and order, food and hydration, andfacilities and detention cells.The results of the study reveal that the problems encountered by a person deprived of libertywere evaluated as “Disagree” in terms of health and medical services, peace and order, foodand hydration, and facilities and detention cells, and there is a measure may propose toaddress the Problem Encountered by Person Deprived of Liberty.This study necessarily recommended improvement and providing additional detentionfacilities for the person deprived of liberty supporting government officials, national agencies,and other authorities. For additional medical personnel, it is important to understand thestructural conditions within PDL facilities. Additional medical facilities increasing jailcongestion have more challenges in access to health services in one of their medical facilities.Additional classroom (for bible teaching and therapy sessions) is necessarily recommended tobuild an additional classroom for treatment. This program’s very important for the persondeprived of liberty to help improve the attitude and spirit to have the will to change himself andthen give him support to improve.
Keywords: Criminology